2015
DOI: 10.1016/bs.mie.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Pull-Down FRET to Dissect the Mechanisms of Biomolecular Machines

Abstract: Spliceosomes are multi-megadalton RNA-protein complexes responsible for the faithful removal of non-coding segments (introns) from pre-messenger RNAs (pre-mRNAs), a process critical for the maturation of eukaryotic mRNAs for subsequent translation by the ribosome. Both the spliceosome and ribosome, as well as many other RNA and DNA processing machineries, contain central RNA components that endow biomolecular complexes with precise, sequence-specific nucleic acid recognition and versatile structural dynamics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Hoskins et al revealed the order of spliceosome assembly during pre-mRNA maturation in cell extract via single-molecule multi-color fluorescence [22,23]. Single-molecule pull-down FRET allowed Nils et al to visualize in real time the splicing of pre-mRNA by the spliceosome [24,25]. Lee et al used a single-molecule co-immunoprecipitation approach to investigate weak interactions between different proteins [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hoskins et al revealed the order of spliceosome assembly during pre-mRNA maturation in cell extract via single-molecule multi-color fluorescence [22,23]. Single-molecule pull-down FRET allowed Nils et al to visualize in real time the splicing of pre-mRNA by the spliceosome [24,25]. Lee et al used a single-molecule co-immunoprecipitation approach to investigate weak interactions between different proteins [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule pull down (SiMPull) and its derivatives SNAP-SiMPull and SiMPull-FRET fuse conventional pull-down assays with single-molecule fluorescence microscopy or single-molecule fluorescence resonance energy transfer (FRET) to allow direct visualization of individual protein complexes. Using these methods, studies have demonstrated the ability to detect single molecules of U1 snRNP and to investigate the dynamic nature of the mammalian target of rapamycin (mTOR)-containing complex (mTORC) dimerization and the selectivity of rapamycin on mTORC stoichiometry. , The ability to understand the dynamics of mTORC1 and mTORC2 is promising as mTOR is a regulatory protein associated with many cellular pathways like mRNA translation, ribosome biogenesis, autophagy, and metabolism. Additionally, mTOR deregulation has been linked to several types of cancer .…”
Section: Novel Methods Supporting Additional Mechanistic and Function...mentioning
confidence: 99%
“…Additionally, mTOR deregulation has been linked to several types of cancer . SiMPull-FRET was utilized to investigate pre-mRNA splicing dynamics and revealed that the spliceosome achieves an accurate initial splice through a biased Brownian ratcheting mechanism. , Because deregulated alternative splicing has been identified in ALS, SMA, AD, and even cancer, the capability to monitor spliceosome dynamics is a strong first step toward understanding the beginning of splicing defects and their proliferation through the cell.…”
Section: Novel Methods Supporting Additional Mechanistic and Function...mentioning
confidence: 99%
“…On the basis of these results, the authors concluded that spliceosome activation proceeds via a Brownian ratchet mechanism, in which ATP hydrolysis by Prp2 unlocks reversible fluctuations in the conformation of the pre-mRNA (and likely other components of the spliceosome), with Cwc25 acting as a pawl that facilitates the first step of splicing by trapping the conformation in which the BP and 5′SS are in close proximity. 143,260…”
Section: Single Molecule Fluorescence Studies Of Rna-protein Assemmentioning
confidence: 99%
“…Further addition of Cwc25 yielded a population of complexes that remained stably in the high-FRET state, which was confirmed by additional experiments to result from C complexes that have completed the first chemical reaction of splicing. On the basis of these results, the authors concluded that spliceosome activation proceeds via a Brownian ratchet mechanism, in which ATP hydrolysis by Prp2 unlocks reversible fluctuations in the conformation of the pre-mRNA (and likely other components of the spliceosome), with Cwc25 acting as a pawl that facilitates the first step of splicing by trapping the conformation in which the BP and 5′SS are in close proximity. , …”
Section: Single Molecule Fluorescence Studies Of Rna-protein Assembliesmentioning
confidence: 99%